OP0039 HOSPITALIZATION AND MORTALITY OUTCOMES IN RHEUMATOID ARTHRITIS PATIENTS WITH LUNG DISEASE. (2nd June 2020) - Pedro, S.; Mikuls, T.; Zhuo, J.; Michaud, K.
Abstract : Background: Pulmonary manifestations such as interstitial lung disease (ILD) and chronic obstructive pulmonary disease (COPD) are frequent extra-articular features that carry a poor prognosis in rheumatoid arthritis (RA). Prior studies have demonstrated that respiratory-related mortality is the most overrepresented cause of death in RA. Objectives: To assess the risk of all-cause and respiratory-related hospitalization and mortality in RA patients with comorbid lung disease (LD) in comparison to those without and the differential risks associated with DMARD treatments. Methods: Eligible RA patients included those enrolled in the Forward Databank with ≥1 year observation after 2000 and had initiated a DMARD. Forward is a large longitudinal rheumatic disease registry in the US. RA patients' diagnoses were rheumatologist-confirmed, and every 6 months participants completed comprehensive questionnaires regarding symptoms, disease outcomes, medications, and clinical events. LD was defined as one of the following: emphysema, asthma, bronchitis, COPD, pleural effusion, fibrosis of the lung, "RA lung", or ILD (England 2019). DMARDs were categorized hierarchically into four groups: csDMARDs, TNFi and NTNFi (bDMARDs), and tsDMARDs. Patients were followed from DMARD initiation until event (death and/or hospitalization) or end of follow-up, whatever came first. Events were validated using medical records and the US National Death Index. Respiratory hospitalizations and deaths were identified with ICD9 (460-519). Events were analyzed using incidence rates (IR) and Cox regression models. Models were adjusted for LD, DMARDs, age, sex, education, HAQ disability, Rheumatic Disease comorbidity index, smoking, pain, glucocorticoids, year of entry, prior bDMARDs and csDMARDs counts and MRC breath scale. Results: Of the 21, 525 eligible RA patients, 13.8% had LD at the time of DMARD initiation. Patients had 59 years old in both groups and 15% were male for LD+ vs 21% for LD-. Patients with LD+ showed worse disease outcomes (HAQ: 1.3 (0.7) vs 1.0 (0.7)) and comorbidities (2.9 (1.9) vs 1.5 (1.4)) overall and for all treatment groups, especially for NTNFi and tsDMARDi. The overall IR of any all-cause or respiratory-related events were higher in LD+ than LD- RA patients and across any DMARD treatments, with NTNFi having higher IR (Figure). In survival analyses, LD+ was associated with an increased risk for all-cause hospitalizations/deaths (HR 1.3; 95% CI 1.1-1.4) and a 3.95-fold increased risk of respiratory-related events (HR 4.0; 3.2-4.9) (Table). These risks did not differ significantly across DMARD treatment groups. Increased age, HAQ disability, comorbidities, glucocorticoids, prior bDMARDs and worse MRC breath scales were associated with an increased risk in both outcomes and smoking in respiratory-specific events. Conclusion: An increased risk of hospitalizations and/or deaths was demonstrated for RA patients with lung disease, most notably a 4-fold increased risk for respiratory-related events. No differences were found between incident DMARD groups. Additional studies accounting for channeling of treatments by baseline health status are needed. References: [1]England BR, et al Arth Care Res . doi:10.1002/acr.24043. Disclosure of Interests: Sofia Pedro: None declared, Ted Mikuls Grant/research support from: Horizon Therapeutics, BMS, Consultant of: Pfizer, Joe Zhuo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Kaleb Michaud Grant/research support from: Janssen